2019
DOI: 10.1177/1040638719880245
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of plasma cell-free DNA levels in dogs with various tumors

Abstract: Circulating cell-free DNA (cfDNA) is extracellular DNA released into the bloodstream by apoptotic or necrotic tumor cells, with cfDNA determination proposed as a noninvasive, sensitive marker for the diagnosis of human cancer. We evaluated cfDNA quantification as a diagnostic and prognostic tool in dogs with various tumors. We quantified plasma cfDNA concentration by absolute real-time PCR of long interspersed nuclear elements in 50 dogs with malignant tumors, 13 dogs with benign tumors or nodules, and 11 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 32 publications
4
50
0
2
Order By: Relevance
“…As in human, cfDNA concentration in dogs is correlated with the severity of the disease and prognosis 16,17,20,53 . Consistently with previous studies, we found that dogs with multicentric lymphoma had significantly higher concentration of total cfDNA than healthy dogs, dogs with non-cancerous diseases and dogs with other cancers 20,51 . Our cfDNA concentrations were in agreement with those of previous studies, although results were highly variable in terms of median cfDNA concentrations, ranging from 4 to 583ng/ml in healthy dogs for example.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As in human, cfDNA concentration in dogs is correlated with the severity of the disease and prognosis 16,17,20,53 . Consistently with previous studies, we found that dogs with multicentric lymphoma had significantly higher concentration of total cfDNA than healthy dogs, dogs with non-cancerous diseases and dogs with other cancers 20,51 . Our cfDNA concentrations were in agreement with those of previous studies, although results were highly variable in terms of median cfDNA concentrations, ranging from 4 to 583ng/ml in healthy dogs for example.…”
Section: Discussionsupporting
confidence: 92%
“…cfDNA is an attractive biomarker in human medicine and particularly in oncology. Thus, it has also been evaluated in different canine diseases 16,17,19,20,[50][51][52][53] . As in human, cfDNA concentration in dogs is correlated with the severity of the disease and prognosis 16,17,20,53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated concentrations of cfDNA have been reported in dogs with cancer, however, this is the first time, to the authors' knowledge, that elevated nucleosome concentrations have specifically been reported in dogs with cancer (13,32,33).…”
Section: Discussionmentioning
confidence: 64%
“…The plasma cfDNA concentration was measured using a quantitative real-time PCR (qPCR) reaction of long interspersed nuclear element-1 (LINE-1), as previously described [14]. The results of this assay were used for the normalization of DNA volume to be used in the qPCR for the BRAF mutation.…”
Section: Quantification Of Cfdna Using the Line-1 Genementioning
confidence: 99%